Penerapan Model Pembelajaran Discovery Learning Dengan Menggunakan Strategi Active Knowledge Sharing Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran IPS Terpadu Pada Siswa Kelas Viii Pk 2 Mts Negeri 1 Surakarta Tahun Ajaran 2015/2016 - Isnaini, Lia; , Prof. Dr. Harsono, SU (2016)
This study aims to improve student learning outcomes in subjects ips integrated PK VIII class 2 MTs N 1 Surakarta through discovery learning model application using a strategy of active learning with knowledge sharing. This study uses action research approach to the design of the classroom action research study conducted in two cycles in which each cycle traversed by 4 (four) stages: (1) planning; (2) implementation; (3) observation; (4) reflection. Methods of data collection used the tests, observation, documentation and field notes. Data analysis technique used is descriptive analysis technique comparative and critical analysis techniques. The results showed that the activity of students has increased from before the procedure until the second cycle, the student activity prior to the act of obtaining a score as much as 11.4 score with a success rate of 29.6%, an increase in the first cycle with the acquisition score as much as 23.3 score level the success of 63%, and increased again in the second cycle with the acquisition score as much as 28.2 score with a success rate of 75.5%. The increase also occurred in student learning outcomes of prior actions to the implementation of the first cycle and the second cycle. Student learning outcomes realm of spiritual attitudes and social behavior before action by 42% and 50.42%, increased in the first cycle with the classical completeness rate of 60.2% and 68.85%, and increased again in the second cycle to the level of classical completeness of 67.6% and 77.85%. Learning outcome domains of knowledge shown by classical completeness before action by 33%, increased in the first cycle of 45%, and increased in the second cycle of 100%. Improved learning outcomes realm of skills demonstrated by classical completeness before action of 41% increase in the first cycle by 45%, and increased in the second cycle of 100%. So it can be concluded that learning through discovery learning model using active knowledge sharing strategies can improve student learning outcomes which include student activities, and the results of class VIII student PK 2 in social studies integrated in MTs N 1 Surakarta. The advice given is that the discovery learning model learning using active knowledge sharing strategy can be used as a reference teacher as a solution to improve student learning outcomes in social studies integrated in class VIII MTs PK 2 N 1 Surakarta.